2009
DOI: 10.1074/jbc.m109.002311
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of Human Pex5·Pex14·PTS1 Protein Complexes Obtained by Small Angle X-ray Scattering

Abstract: The Pex5p receptor recognizes newly synthesized peroxisomal matrix proteins which have a C-terminal peroxisomal targeting signal to the peroxisome. After docking to protein complexes on the membrane, these proteins are translocated across the membrane. The docking mechanism remains unclear, as no structural data on the multicomponent docking complex are available. As the interaction of the cargo-loaded Pex5p receptor and the peroxisomal membrane protein Pex14p is the essential primary docking step, we have inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 39 publications
2
35
1
Order By: Relevance
“…PEX14 can homo-oligomerize and a stable complex with the stoichiometry of 1:5 for PEX5-PEX14 was isolated from rat liver (Gouveia et al, 2000). Consistent with this, titration studies with purified recombinant proteins gave a stoichiometry of 1:6 for PEX5-PEX14 (Shiozawa et al, 2009). …”
Section: Stoichiometry Affinity and Order Of Binding Interactions Amsupporting
confidence: 64%
See 1 more Smart Citation
“…PEX14 can homo-oligomerize and a stable complex with the stoichiometry of 1:5 for PEX5-PEX14 was isolated from rat liver (Gouveia et al, 2000). Consistent with this, titration studies with purified recombinant proteins gave a stoichiometry of 1:6 for PEX5-PEX14 (Shiozawa et al, 2009). …”
Section: Stoichiometry Affinity and Order Of Binding Interactions Amsupporting
confidence: 64%
“…Controversy exists as to whether PEX5 binds cargo as a monomer (Costa-Rodrigues et al, 2005), dimer or tetramer (Madrid et al, 2004;Moscicka et al, 2007). However, more recent studies are consistent with a monomeric solution structure (Shiozawa et al, 2009).…”
Section: Stoichiometry Affinity and Order Of Binding Interactions Ammentioning
confidence: 99%
“…It was shown that each of the seven WXXX(F/Y) motifs of the human PTS1 receptor can interact with the highly conserved N-terminal domain (NTD) of Pex14 with equilibrium dissociation constants in the nanomolar range (12,13). A recent biophysical study showed that the presence of multiple WXXX(F/Y) motifs in the N terminus of Pex5 allows the formation of higher order complexes with the Pex14-NTD in vitro, although it is not clear whether this also reflects the situation in peroxisomes in vivo (14,15). Interestingly, human Pex19, which is supposed to act as an import receptor/chaperone for peroxisomal membrane proteins, binds competitively to the same surface in Pex14-NTD via an amphipathic helix-forming pentapeptide sequence (16).…”
Section: In Human Cells This Interaction Is Mediated By Seven Consermentioning
confidence: 99%
“…All spectra were processed with NMRPipe (27) and analyzed in Sparky (33). NMR spectra for assignment and structural determination of the Pex14-(16 -80)⅐Pex5-(57-71) complex were acquired on a sample containing 13 C, 15 N-labeled Pex14-(16 -80) bound to unlabeled Pex5-(57-71). Protein backbone and side chain assignments were obtained using standard tripleresonance experiments (28).…”
Section: Construction Of Pex5 Fragment Expression Vectors-formentioning
confidence: 99%
“…Structurally, it can be divided into two domains: a C-terminal half containing seven tetratricopeptide repeats organized into a ring-like structure (13,14) and a natively unfolded N-terminal half (11,15). Although it has been shown that the C-terminal half of PEX5 has a crucial role in the interaction with the PTS1 (13,14), it is becoming increasingly apparent that the N-terminal half of PEX5 also contributes to the interaction with cargo proteins (16 -20).…”
mentioning
confidence: 99%